Dispersion of synonymous codon usage patterns in hepatitis E virus genomes derived from various hosts. (1st July 2022) - Wang, Xin; Sun, Jing; Zheng, Yueyan; Xie, Fuqiang
Abstract: Hepatitis E virus (HEV) is an important zoonotic pathogen infecting a wide range of host species. It has a positive‐sense, single‐stranded RNA genome encoding three open reading frames (ORFs). Synonymous codon usages of viruses essentially determine their survival and adaptation to susceptible hosts. To better understand the interplay between the ever‐expanding host range and synonymous codon usages of HEV, we quantified the dispersion of synonymous codon usages of HEV genomes isolated from different hosts via Vs calculation and information entropy. HEV ORFs show species‐specific synonymous codon usage patterns. Ruminant‐derived HEV ORFs own the most synonymous codons with stable usage patterns ( Vs value <0.1) which leads to the stable overall codon usage patterns ( R value being close to zero). Swine‐derived HEV ORFs own more concentrated synonymous codons than those from wild boar. Compared with HEV strains isolated from other hosts, the human‐derived HEV exhibits a distinct pattern at the overall codon usage ( R < 0). Generally, ORF1 contains more synonymous codons with stable usage patterns ( Vs < 0.1) than those of ORFs 2 and 3. Moreover, ORF3 contains more synonymous codons with varied patterns ( Vs > 1.0) than ORFs 1 and 2. The host factor serving as one of the evolutionary dynamics probably influences synonymous codon usage patterns of the HEV genome. Taken together, synonymous codons with stable usage patterns in ORF1 might help to sustain the infection, while that with varied usage patterns in ORF3 may facilitate cross‐species infection and expand the host range.